beta-Xylosidases from filamentous fungi: an overview - Knob, A. [UNESP]; Terrasan, C. R. F. [UNESP]; Carmona, E. C. [UNESP] (Springer, 2010)
beta-Xylosidases are hydrolytic enzymes which play an important role in xylan degradation, hydrolyzing xylobiose and xylooligosaccharides to xylose from the non-reducing end. Filamentous fungi are particularly interesting producers of this enzyme from an industrial point of view, due to the fact that they secrete beta-xylosidases into the medium. Besides, fungal beta-xylosidases are highly advantageous for their elevated activity levels and specificity. Interest in xylanolytic enzymes has been increasing, for their possible application in many biotechnological processes. This fact has driven the isolation, purification and characterization of several beta-xylosidases. In this review, the mechanisms of action, substrate specificities, physicochemical characteristics, regulation at molecular level, molecular cloning and classification of filamentous fungal beta-xylosidases are described. The potential industrial applications of fungal beta-xylosidases will also be presented.
Keywords: beta-Xylosidases; Filamentous fungi; Physicochemical characteristics; Mechanisms of action; Biotechnological applications